Magnesium(II) Complexes of Triazene-1-Oxides - Sharma, Ramadhar; Thakur, A.K.; Bilas Rai, Shiva (Asian Journal of Chemistry, 2010)
Magnesium(II) derivatives of triazene-1-oxides (TH) have been reported. The preparation of the derivatives has been achieved by interacting alcoholic solution of (TH) with (i) magnesium chloride-hydroxide and (ii) magnesium metal magnesium oxide. Mixed-ligand complexes of magnesium(II) were prepared by reacting MgT22H2O chelates with o-phenanthroline/dipyridyl in 1 : 1 molar ratio in acetone. Structural investigations have been done by elemental analyses, conductance, molecular weight and I.R. spectral studies.